The Impact of Translanguaging on the Reading Comprehension Lessons in 3rd Forms in the Kabarhe North Territory - Muyaya, Michel Tshikisha; Tembue , Mathieu Joseph Wa Ololo (Journal of Education and Practice, 2024)
Purpose: The objective was to examine the impact of translanguaging as a pedagogical strategy on the understanding of texts written in English during reading comprehension lessons Methodology: This research is a quasi-experimental study with two groups of learners. One group, the experimental class, was submitted to the translanguaging strategy while the other group, the control class, did not undergo any treatment. Findings: The results of the study proved that 1) very few learners in both classes hardly understood texts written in English during reading comprehension lessons; 2) learners were frustrated, stressed, anxious because of the exclusive use of the English language, 3) owing to the translanguaging strategy, learners of the experimental class highly improved their understanding of texts written in English during reading comprehension lessons. This was not the case with learners from the control class; 3) the comparison of mean scores of the pre-test and the post-test showed that translanguaging impacted positively the teaching of reading comprehension lessons. Unique Contribution to Theory, Policy and Practice: from the findings, learners and teachers will be using deliberately their linguistic repertoire, and the researcher expects teachers, and the D.R.C. Government, to implement this strategy in the teaching of the reading comprehension lesson for a better understanding of texts written in English. The translanguaging strategy will help learners to be more motivated and less frustrated towards the learning of English texts and the mastery of English as an additional language. There is an expectation of the elimination of frustration, stress, hate and anxiety, and the amelioration of motivation and interest in the English language